Determining the Dimensions of Service Quality Redundancy in Banking - Mohseni Mehr, Kiomars; Niki Esfahlan, Hakimeh; Aali, Samad (Management Strategies and Engineering Sciences, 2023)
Today, banks and credit institutions are among the most important sectors of the economy, responsible for organizing the transfer of funds. In the current situation, where all Iranian banks offer similar products, what can lead to customer attraction, loyalty, and satisfaction is being a leader in providing innovative banking services and maintaining effective and rapid interaction. Therefore, defining the dimensions of service quality redundancy in banking is crucial for the success of banks. This study aims to determine the dimensions of service quality redundancy in banking through the method of meta-synthesis. Based on the research findings, the dimensions of electronic service quality include website appearance, ease of use, reliability, security, and other factors related to the provision of electronic services. The factors influencing banking service quality are: reliability, responsiveness, empathy, security, and continuous improvement. These factors ultimately lead to functional, geographical, and technological and informational redundancy.